COMPENSATION, MOTIVATION, AND JOB SATISFACTION EFFECTS ON EMPLOYEE PERFORMANCE IN THE COMPANY - Festus Evly R.I. Liow; Akhmad Nur Zaroni; Sri Gustini; Mustika Wati Alfia Ningtyas; Liswandi Liswandi (Jurnal Ekonomi, 2023)
Compensation, motivation, and job satisfaction are all factors that influence employee performance. Compensation is the number of benefits that an organization provides to employees in exchange for hiring them. This study used a qualitative research method in the form of literature studies or library research. To examine a theory, this type of research compares several existing theories in the literature or the results of previous research contained in scientific articles relevant to the field of human resource management. All cited scientific articles were located using Mendeley and Google Scholar literacy data searches. Based on the review and discussion of the literature, a conclusion can be drawn. 1. Employee compensation for leaders has a significant impact on company performance. 2. Employee motivation by leaders has a significant impact on the quality of employee performance. 3. Workplace satisfaction has a significant impact on employee performance quality.